Epicardial Adipose Tissue Measured From Computed Tomography Predicts Cardiac Resynchronization Therapy Response in Patients With Non-ischemic Systolic Heart Failure - Qin, Hui-yuan; Wang, Cheng; Qian, Duo-duo; Cui, Chang; Chen, Ming-long (Frontiers in Cardiovascular Medicine, 2021)
Background: Epicardial adipose tissue (EAT) has been linked with the pathogenesis of heart failure (HF). Limited data have been reported about the clinical value of EAT for cardiac resynchronization therapy (CRT) in Non-ischemic systolic HF. We aimed to explore the values of EAT measured from computed tomography to predict the response to CRT in patients with Nonischemic systolic HF. Methods: Forty-one CRT patients were consecutively recruited for our study. All patients received both gated resting SPECT myocardial perfusion imaging (MPI)and dual-source multidetector row computed tomography (CT) scans. EAT thickness was assessed on both the parasternal short and horizontal long axis views. The area of EAT was calculated at the left main coronary artery level. Left ventricular systolic mechanical dyssynchrony (LVMD) was measured by phase standard deviation (PSD) and phase histogram bandwidth (PBW). The definition of CRT response was an improvement of 5% in LVEF at six months after CRT implantation. Results: After six months of follow-up, 58.5% (24 of 41) of patients responded to CRT. A greater total perfusion deficit (TPD) was observed in the left ventricle and a narrower QRS complex was observed in the nonresponse group than in the response group (p<0.05). Meanwhile, the systolic PSD and systolic PBW were statistically greater in the CRT group with no response than in the response group (p<0.05). Meanwhile, the baseline QRS duration, TPD, systolic PSD, systolic PBW, EAT thicknesses of the left ventricular (LV) apex, right atrioventricular (AV) groove and left AV groove were all significantly related to the CRT response in the univariate logistic regression analysis. Furthermore, the QRS duration and EAT thicknesses of the right AV groove and left AV groove were independent predictors of CRT response in the multivariate logistic regression analysis. Conclusions: The EAT thickness of the left AV groove in patients with Nonischemic systolic HF is associated with the TPD of LV and LV systolic dyssynchrony. The EAT thickness of the AV groove has good predictive value for the CRT response in patients with Nonischemic systolic HF.